ANALISIS PELAKSANAAN KAMPANYE 3M (MEMAKAI MASKER, MENCUCI TANGAN DAN MENJAGA JARAK) DI KABUPATEN PACITAN SELAMA MASA PANDEMI (Jurnal Riset Manajemen Akuntansi Indonesia, 2025)
This study aims to analyze the causes of violations of the 3M health protocol (washing hands with running water and soap, wearing masks, maintaining distance and formulating efforts to increase awareness of the 3M health protocols (washing hands with running water and soap, wearing masks, maintaining distance). to the community in Pacitan Regency. This research is included in descriptive qualitative research. The research location is in Pacitan Regency, during May – June 2021. Data collection techniques are by means of interviews, observations and documentation. The results of data collection are reduced, presented and concluded. The results of the interview showed that knowledge about the 3M health protocol was good, only their behavior was not disciplined because they had not been able to breathe, hand washing facilities were not yet available and adequate, often the area of ​​activity was not comparable between visitors and the size of the place, finally they had difficulty keeping their distance. Efforts to increase awareness of the 3M health protocol (washing hands with running water and soap, wearing masks, maintaining distance) in the community are expected to be able to make people aware of behavioral changes, so as to reduce the rate of transmission of Covid -19 in Pacitan Regency.
Keywords: Wearing a Mask; Washing Hands; Keeping a Distance; 3M